Methodological aspects for the preparation of future teachers of fine arts - Sotska, Halyna; Kuzmenko, Halyna (ScienceRise: Pedagogical Education, 2019)
The article reveals methodological principles for the preparation of future teachers of fine arts for individual pedagogical activity. It was demonstrated, that the preparation should be carried out on the basis of a system, competence, integration, creativity and activity approach. A substantiation of concepts from the above-mentioned approaches in the preparation of future teachers of fine arts was made, which consideration should contribute to innovative alterations in the general education system of specialists in the field of fine arts in higher education institutions. The system approach is considered by the authors as a purposeful and clearly organized method to achieve the determined goal. It envisages a combined consecutive work of students and teachers, managing the educative process, it ensures the integrity, efficiency and resulting quality of the educational process, creating conditions for future teachers to achieve a combination of new qualities, necessary in an individual professional occupation. The competence oriented approach is defined by the authors as a shaped individual quality of a future teacher of fine arts, specifying the extent of his or her knowledge and qualification. The introduction of the competence approach envisages the deposition of cognitive accents of students’ readiness for independent work to competent accents, which are based on value priorities of a person, particularities of his or her experience and beliefs, and ensures the readiness for creative and productive individual work. The integration approach envisages the alteration of accents in the construction of the pedagogical process from a subject-centric structure to a poly-centric one, by overcoming disunity, fragmentation of professional knowledge, differentiated according to different academic disciplines, and contributes to the creation of an integral thinking style. The creativity approach envisages depriving the educational process in higher education institutions from patterns and standards, as well as giving preference to an active search for non-standard solutions, methods, forms, approaches for improving the education of students in order to achieve a higher professional level. The introduction of the activity approach, where the teacher is considered not as a “translator”, but as a coordinator for students in methods of obtaining and digesting new information, by assisting the students to get involved in different forms of creative artistic and pedagogical occupation, which demonstrates their activity as an universal “instrument” of self-fulfillment of the artistic and creative potential, which ensures the readiness formation for an active life position and a continuous education during the whole life